Insight into impact of size and shape on optoelectronic properties of InX (X = As, Sb, and P) semiconductor nanoparticles: a theoretical study - Sherka, Gebru Tesfaye; Berry, Habte Dulla (Frontiers in Physics, 2024)
Because of their quantum confinement effects and adjustable features, semiconductor nanoparticles have attracted a lot of attention for their various uses in optoelectronic devices. This study investigates how size and shape variations affect the optoelectronic properties of semiconductor nanoparticles InX (X = As, Sb, and P). Using unified thermodynamics modeling, it explores the effects of these nanoparticles' diameters on their electronic band structures, optical properties, and charge carrier dynamics. The inquiry focuses on InX nanoparticles with different sizes and nanostructure morphologies. By examining electronic band structures, the density of states, and optical absorption spectra, the size-dependent quantum confinement processes that govern the optical band gap transitions and excitonic behaviors in these semiconductor nanoparticles were made clear. Also, the influence of the shape of the nanoparticles on carrier mobility and electronic band alignment is investigated, offering insights into the possibility of controlling the morphology to customize optoelectronic capabilities. This theoretical analysis indicates that altering the optoelectronic properties of InX semiconductor nanoparticles is mostly dependent on their size and shape. Smaller nanoparticles show stronger quantum size effects, which lead to improved exciton confinement and blue shifts in the optical absorption spectra. Shape-dependent differences in the density of states and electronic band structures indicate the impact of morphology on the dynamics and recombination of charge carriers in the nanoparticles.In conclusion, this work provides important insights for the design and optimization of semiconductor nanomaterials for photovoltaic, sensing, and light-emitting applications by thoroughly examining the impact of size and shape on the optoelectronic properties of InX semiconductor nanoparticles.